The role of bi-polar plate design and the start-up protocol in the spatiotemporal dynamics during solid oxide fuel cell anode reduction - Heenan, Thomas M. M.; Nabavi, Seyed Ali; Erans, María; Robinson, James B.; Kok, Matthew D. R.; Maier, Maximilian; Brett, Daniel J. L.; Shearing, Paul R.; Manovic, Vasilije (MDPI, 2020)
Start-up conditions largely dictate the performance longevity for solid oxide fuel cells (SOFCs). The SOFC anode is typically deposited as NiO-ceramic that is reduced to Ni-ceramic during start-up. Effective reduction is imperative to ensuring that the anode is electrochemically active and able to produce electronic and ionic current; the bi-polar plates (BPP) next to the anode allow the transport of current and gases, via land and channels, respectively. This study investigates a commercial SOFC stack that failed following a typical start-up procedure. The BPP design was found to substantially affect the spatiotemporal dynamics of the anode reduction; Raman spectroscopy detected electrochemically inactive NiO on the anode surface below the BPP land-contacts; X-ray computed tomography (CT) and scanning electron microscopy (SEM) identified associated contrasts in the electrode porosity, confirming the extension of heterogeneous features beyond the anode surface, towards the electrolyte-anode interface. Failure studies such as this are important for improving statistical confidence in commercial SOFCs and ultimately their competitiveness within the mass-market. Moreover, the spatiotemporal information presented here may aid in the development of novel BPP design and improved reduction protocol methods that minimize cell and stack strain, and thus maximize cell longevity
Keywords: degradation; SEM; Raman; X-ray CT; reduction; REDOX; Ni–YSZ; anode; fuel cell; SOFC